UMUR FORMASI NAMBO DI SULAWESI TENGAH DENGAN ACUAN KHUSUS FOSIL MOLUSKA - Hasibuan, Fauzi; Kusworo, A. (Pusat Survei Geologi, 2008)
The Nambo Formation distributed in the eastern of Sulawesi is well exposed along the Nambo River, Luwuk, Central Sulawesi. In this locality it consists of calcareous grey shale, with some calcareous sandstone interbeds, about 50 m thick. The molluscan fauna is composed among others of Retroceramus (R.) haasti, Malayomaorica malayomaorica, B. aucklandica similis, Belemnopsis moluccana, B. galoi, B. stolleyi and B. mangolensis. It is concluded that based on the molluscan faunal assemblage, the age of the formation is Tithonian. It is correlable with the upper part of the Buya Formation in the Sula Islands. Keywords : Nambo Formation, molluscs, Tithonian, Nambo River, Central Sulawesi, Buya Formation, Retroceramus, Malayomaorica, Belemnopsis.